Dataset associated with “Context dependency of disease-mediated competitive release in bat assemblages following white-nose syndrome” - Bombaci, Sara P.; Russell, Robin E.; St. Germain, Michael J.; Dobony, Christopher A.; Ford, W. Mark; Loeb, Susan C.; Jachowski, David S. (Colorado State University. Libraries, 2021)
White-nose syndrome (WNS) has caused dramatic declines of several cave-hibernating bat species in North America since 2006, which has increased the activity of non-susceptible species in some geographic areas or during times of night formerly occupied by susceptible species - indicative of disease-mediated competitive release (DMCR). Yet, this pattern has not been evaluated across multiple bat assemblages simultaneously or across multiple years since WNS onset. We evaluated whether WNS altered spatial and temporal niche partitioning in bat assemblages at four locations in the eastern United States using long-term datasets of bat acoustic activity collected before and after WNS arrival. Activity of WNS-susceptible bat species decreased by 79-98% from pre-WNS levels across the four study locations, but only one of our four study sites provided strong evidence supporting the DMCR hypothesis in bats post-WNS. These results suggest that DMCR is likely dependent on the relative difference in activity by susceptible and non-susceptible species groups pre-WNS and the relative decline of susceptible species post-WNS allowing for competitive release, as well as the amount of time that had elapsed post-WNS. Our findings challenge the generality of WNS-mediated competitive release between susceptible and non-susceptible species and further highlight declining activity of some non-susceptible species, especially Lasiurus borealis, across three of four locations in the eastern US. These results underscore the broader need for conservation efforts to address the multiple potential interacting drivers of bat declines on both WNS susceptible and non-susceptible species.
Dataset of bat acoustic detections across four study areas in the US to study the impact of white-nose syndrome on bat community interactions. Data collected from 2003-2017 at four study locations in the United States, including Fenrnow Experimental Forest, WV; Fort Pickett, VA; Fort Drum, NY; two locations in Wisconsin.
Department of Fish, Wildlife, and Conservation Biology
Keywords: bat communities; competition; competitive release; disease ecology; niche partitioning; North American bats; Pseudogymnoascus destructans; WNS